2020
DOI: 10.1111/obr.13099
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and duration of excess of post‐exercise oxygen consumption between high‐intensity interval and moderate‐intensity continuous exercise: A systematic review

Abstract: Summary The present systematic review examined the effect of exercise intensity (high‐intensity interval exercise [HIIE] vs. moderate‐intensity continuous exercise [MICE] vs. sprint interval exercise [SIE]) on excess post‐exercise oxygen consumption (EPOC). Twenty‐two studies were included in the final evaluation. The retrieved investigations were split into studies that analysed short‐duration (until 3 h) and long‐duration (more than 3 h) EPOC. Studies that subtracted the baseline energy expenditure (EE) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
(125 reference statements)
0
11
0
1
Order By: Relevance
“… 34 , 54 In contrast, HIIT increased excess postexercise oxygen consumption (EPOC) compared to MICT during the slow phase of O 2 kinetics in the recovery phase (i.e., from 30 min to 22 h after the end of the training session). 55 This occurs due to greater postexercise fat utilization to sustain energy demands while glycogen resynthesis occurs 56 and occurs through significant increases in circulating hormones that promote fat oxidation (i.e., catecholamines and growth hormone), 56 although the results are conflicting. 45 Thus, through different physiological mechanisms, our results demonstrate that combining reduced energy intake with physical exercise (i.e., COMB training or HIIT) is a useful strategy for both weight- and FM-loss programs for obese adults.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 54 In contrast, HIIT increased excess postexercise oxygen consumption (EPOC) compared to MICT during the slow phase of O 2 kinetics in the recovery phase (i.e., from 30 min to 22 h after the end of the training session). 55 This occurs due to greater postexercise fat utilization to sustain energy demands while glycogen resynthesis occurs 56 and occurs through significant increases in circulating hormones that promote fat oxidation (i.e., catecholamines and growth hormone), 56 although the results are conflicting. 45 Thus, through different physiological mechanisms, our results demonstrate that combining reduced energy intake with physical exercise (i.e., COMB training or HIIT) is a useful strategy for both weight- and FM-loss programs for obese adults.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been reported that energy expenditures during low-volume exercise modalities, including LOW-HIIT [ 71 ], 1-RT [ 72 ] and WB-EMS [ 73 ], are quite small, ranging around 120–150 kcal per exercise session. However, it has also been documented that HIIT exercises are particularly effective to stimulate excess post-exercise oxygen consumption (EPOC), a valid measure to quantify elevated energy expenditure after cessation of exercise, which has been associated with higher fat loss over a longer period of time [ 74 , 75 , 76 ]. Furthermore, it has recently been shown that both HIIT and traditional RT resulted in increased resting metabolic rate for at least 14 h post-exercise in healthy women [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endurance exercise can promote the release of these hormones [66], promoting lipolytic processes and releasing vitamin D metabolites from the adipose tissue. Moreover, a systematic review showed that all exercise protocols (high-intensity interval exercise, moderate-intensity continuous exercise, and sprint interval exercise) can generate elevated energy expenditure through excessive post-exercise oxygen consumption (EPOC) [67]. Exercise-induced energy deficit has the most potent effect on endogenous lipid metabolism, elevating plasma triacylglycerol concentration and increasing plasma fatty acid mobilization and oxidation the day after performing endurance exercises [68].…”
Section: Mechanismmentioning
confidence: 99%